2013
DOI: 10.4137/bcbcr.s11118
|View full text |Cite
|
Sign up to set email alerts
|

Dose Distribution in the Heart and Cardiac Chambers following 4-field Radiation Therapy of Breast Cancer: a Retrospective Study

Abstract: Purpose:To evaluate cardiac doses in breast cancer patients with stage II/III treated with 4-field radiotherapy based on computed tomography (CT) dose planning.Methods and Materials:Based on archived CT images, whole heart and cardiac chamber radiation doses were analyzed in 216 (111 left-sided and 105 right-sided) mastectomized or lumpectomized breast cancer patients treated at a single institution, the Norwegian Radium Hospital, between 2000–2002. Individual dose volume histograms for the whole heart and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(72 reference statements)
2
7
0
1
Order By: Relevance
“…For the 106 patients in our cohort where detailed dosimetric data were available, the median value for the mean cardiac dose was 3.0 Gy (left-sided BC), and 1.5 Gy (right-sided BC), considerably lower than in other populations studied [9,14,15]. Taylor et al demonstrated a higher cardiac mortality rate with older, as compared to more recent, radiation techniques [15].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For the 106 patients in our cohort where detailed dosimetric data were available, the median value for the mean cardiac dose was 3.0 Gy (left-sided BC), and 1.5 Gy (right-sided BC), considerably lower than in other populations studied [9,14,15]. Taylor et al demonstrated a higher cardiac mortality rate with older, as compared to more recent, radiation techniques [15].…”
Section: Discussionmentioning
confidence: 94%
“…The breast/chest wall received a total dose of 50 Gy given in 25 fractions over five weeks. After breast conserving surgery, women below the age of 50 received an electron boost of 10-16 Gy to the tumour bed (6)(7)(8)(9)(10)(11)(12). After mastectomy, all stage III patients and women with stage II with positive resection margins were given a bolus covering the chest wall, the remaining patients received a bolus covering the mastectomy scar with a 3 cm margin.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cardiac chambers exposed to radiation may vary by tumor side, we also matched by tumor side. 14, 15 Controls were required to have follow-up (index interval) equivalent to or greater than the time from radiotherapy to HF diagnosis of the corresponding case.…”
Section: Methodsmentioning
confidence: 99%
“…Gagliardi et al, dans leur modèle prédictif de la toxicité cardiaque basé sur une population de 809 patientes traitées pour un cancer du sein, ont exprimé que lorsque le volume de coeur recevant une dose supérieure à 25 Gy (V 25Gy ) restait inférieur à 10 %, la probabilité de mortalité cardiaque 15 ans après la radiothérapie était de moins de 1 % [34,35]. Des recommandations en ont été déduites, comme par le groupe national norvégien du cancer du sein, qui a préconisé un V 25Gy cardiaque de moins de 5 %, ou le groupe danois un V 40Gy (volume recevant 40 Gy) de moins de 5 % et un V 20Gy (volume recevant 20 Gy) de moins de 10 % [36]. Ces valeurs ne sont cependant pas extrapolables à tous les centres car elles dépendent fortement de la technique standard locale d'irradiation.…”
Section: Faisceaux Tangentiel Et Mammaire Interne Séparésunclassified